Some New Type Sigma Convergent Sequence Spaces and Some New Inequalities - Kuddusi Kayaduman; Mehmet Şengönül (The Scientific World Journal)
We have discussed some important problems about the spaces V~σ and V~0σ of Cesàro sigma convergent and Cesàro null sequence.